An integrin from oyster Crassostrea gigas mediates the phagocytosis toward Vibrio splendidus through LPS binding activity. Issue 1 (November 2015) - Jia, Zhihao; Zhang, Tao; Jiang, Shuai; Wang, Mengqiang; Cheng, Qi; Sun, Mingzhe; Wang, Lingling; Song, Linsheng
Abstract Integrins are a family of cell adhesion molecules which play important roles in the regulation of cell adhesion, migration, proliferation, apoptosis and phagocytosis. In the present study, the immune function of an integrin from the oyster Crassostrea gigas (designated CgIntegrin) was characterized to understand the regulatory mechanism of hemocyte phagocytosis toward different microbes. The full-length cDNA of CgIntegrin was 2571 bp with an open reading frame (ORF) of 2397 bp, encoding a polypeptide of 799 amino acids. The mRNA transcripts of CgIntegrin were predominantly detected in hemocytes, gonad and adductor muscle, while lowly in hepatopancreas, mantle and gill. The mRNA expression level was up-regulated at 6 h post lipopolysaccharide (LPS) stimulation (p < 0.01), while no significant change was observed after peptidoglycan (PGN) stimulation. The oyster hemocytes with relative high CgIntegrin expression level exhibited different phagocytic abilities towards different microorganism and particles, such as Gram-positive bacteria Vibrio splendidus, Gram-negative bacteria Staphylococcus aureus and latex beads. Moreover, the phagocytic rate towards V. splendidus was significantly decreased after the blockade of CgIntegrin using the polyclonal antibody. The recombinant CgIntegrin (rCgIntegrin) displayed agglutinating activity towards V. splendidus but not S. aureus and Y. lipolytica. It also exhibited a higher binding affinity towards LPS (compared to rTrx group) in a dose-dependent manner with the apparent dissociation constant (Kd) of 5.53 × 10−6 M. The results indicated that CgIntegrin served as a pattern recognition receptor with LPS binding activity, which could directly bind to V. splendidus and enhance the phagocytosis of oyster hemocytes.